Prognostic significance of an 11-gene RNA assay in archival tissue of cutaneous melanoma stage I–III patients. (January 2021) - Gambichler, Thilo; Tsagoudis, Konstantinos; Kiecker, Felix; Reinhold, Uwe; Stockfleth, Eggert; Hamscho, Rami; Egberts, Friederike; Hauschild, Axel; Amaral, Teresa; Garbe, Claus
Abstract: Purpose: The purpose of this study was to validate the results of an 11-gene expression profiling (GEP) assay which aims to improve the precision of individual prognosis beyond conventional American Joint Committee on Cancer staging for patients with cutaneous melanoma. Methods: The reverse transcriptase polymerase chain reaction test of 11 prospectively selected genes was performed on 291 formalin-fixed, paraffin-embedded primary tumours of patients with stage I–III cutaneous melanoma. The expression levels of eight prognostic and three reference genes were used in a predefined algorithm to calculate a numerical score (−0.84 to 3.53) and then assign each patient to a preselected risk group (low versus high score) for melanoma-specific survival (MSS). Results: One hundred twenty-seven patients were allocated to the low-score group, with a corresponding five-year disease-free survival (DFS) and MSS of 95% and 99%, respectively. 164 patients were allocated to the high-score group, with a corresponding five-year DFS and MSS of 78% and 88%. Continuous regression analysis demonstrated decreasing MSS probabilities with increasing scores. In a multivariate cox regression, only the 11-GEP, tumour thickness and age were statistically associated with MSS (p = 0.0068, 0.002 and 0.0159). Conclusions: The 11-GEP has been validated as an independent predictor of outcome for melanoma patients. More specifically, using an 11-GEP score cut-off of ≤0, the assay can identify patient cohorts with 10-year survival probabilities well above 90%. This information may be used in the decision-making for a potential adjuvant therapy. Highlights: The 11-gene expression profiling (GEP) score enables more precise prognosis than the American Joint Committee on Cancer classification. Patients with low risk for relapse and death can be detected in stage II and III. The 11-GEP assay serves to select high-risk patients for adjuvant therapy. This assay appears to be of significant translational relevance.